Multi-mtDNA Variants May Be a Factor Contributing to Mitochondrial Function Variety in the Skin-Derived Fibroblasts of Leber's Hereditary Optic Neuropathy Patients - Yao, Shun; Zhou, Qingru; Yang, Mingzhu; Li, Ya; Jin, Xiuxiu; Guo, Qingge; Yang, Lin; Qin, Fangyuan; Lei, Bo (Frontiers in Molecular Neuroscience, 2022)
Heterogeneity is a major feature of Leber’s hereditary optic neuropathy (LHON) and has a significant impact on the manifestation and diagnosis of the disease. This study explored whether multiple variations in mitochondrial genes were associated with the heterogeneity, mainly phenotypic heterogeneity. Ophthalmic examinations were conducted in two probands with LHON with G11778A and multiple mitochondrial gene (mtDNA) variants. Skin fibroblast cell lines were generated from patients and age- and sex-matched controls. ROS levels, mitochondrial membrane potential, cell energy respiration and metabolic functions were measured. Flow cytometry and cell viability tests were performed to evaluate the cell apoptosis levels and fate. We found that cells with more mtDNA variants had higher ROS levels, lower mitochondrial membrane potential and weaker respiratory function. Flow cytometry and cell viability testing showed that multiple mtDNA variants are associated with different levels of cell viability and apoptosis. In conclusion, we found that skin-derived fibroblast cells from G11778A LHON patients could be used as models for LHON research. Multi-mtDNA variants contribute to mitochondrial function variety, which may be associated with heterogeneity in patients with LHON.